Transcriptomic Time-Series Analyses of Gene Expression Profile During Zygotic Embryo Development in Picea mongolica - Yan, Jia; buer, Ha; Wang, Ya ping; zhula, Gegen; Bai, Yu´e (Frontiers in Genetics, 2021)
Zygotic embryogenesis is a critical process during seed development in gymnosperms. However, knowledge on the genome-wide transcriptional activation that guides this process in conifers is limited，especially in Picea mongolica. This tree species is endemic to semi-arid habitats of Inner Mongolia in China. To extend what is known about the molecular events underpinning its zygotic embryogenesis, comparative transcriptomic analyses of gene expression in zygotic embryos were performed by RNA sequencing in P.mongolica. Our results show that most changes in transcript levels occurred in the early embryonic pattering determination and mature embryos formation. Transcripts related to embryogenic competence, cell division pattern, hormones and stress response genes were identified during embryogenesis. Auxin is essential for early embryo patterning and pre-cotyledon embryonic formation. However, ABA is a major regulator of embryo maturation. Moreover, we found that methylation-related gene expression was associated with early- stage embryos, the late embriogenesis abundant protein and storage/energy-related genes activation with late and mature embryos. Furthermore, network analysis revealed stage-specifc and multi-stage gene expression clusters during embryogenesis. WOX, MYB, HLH and AP2 transcription factors seems more relevant during different stages of embryogenesis. Our results provide large-scale and comprehensive transcriptome data for embryo development in P. mongolica. These data will lay a foundation for the protection and utilization of P. mongolica resources.